2015
DOI: 10.1371/journal.pone.0129481
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyls Induce Mitochondrial Dysfunction in SH-SY5Y Neuroblastoma Cells

Abstract: Chronic exposure to polychlorinated biphenyls (PCBs), ubiquitous environmental contaminants, can adversely affect the development and function of the nervous system. Here we evaluated the effect of PCB exposure on mitochondrial function using the PCB mixture Aroclor-1254 (A1254) in SH-SY5Y neuroblastoma cells. A 6-hour exposure to A1254 (5 μg/ml) reduced cellular ATP production by 45%±7, and mitochondrial membrane potential, detected by TMRE, by 49%±7. Consistently, A1254 significantly decreased oxidative phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…As a result, FCCP uncouples respiration from ATP synthesis allowing determination of the maximal respiratory capacity of the electron transport chain only limited by substrate supply. In our system, FCCP completely restored basal respiration levels in SH-SY5Y cells and increased OCR values in~60% in DIV7 neurons, consistent with previous findings [39,40]. The difference in the FCCP response between SH-SY5Y and primary neurons likely reflects neuronal differentiation, as it has been reported that while maximal respiration did not increase above basal levels in nondifferentiated cells, FCCP-induced OCR values were significantly higher in differentiated neurons [39].…”
Section: Aβ42 Induces Mitochondria-mediated Changes In Neuronal Metabsupporting
confidence: 91%
“…As a result, FCCP uncouples respiration from ATP synthesis allowing determination of the maximal respiratory capacity of the electron transport chain only limited by substrate supply. In our system, FCCP completely restored basal respiration levels in SH-SY5Y cells and increased OCR values in~60% in DIV7 neurons, consistent with previous findings [39,40]. The difference in the FCCP response between SH-SY5Y and primary neurons likely reflects neuronal differentiation, as it has been reported that while maximal respiration did not increase above basal levels in nondifferentiated cells, FCCP-induced OCR values were significantly higher in differentiated neurons [39].…”
Section: Aβ42 Induces Mitochondria-mediated Changes In Neuronal Metabsupporting
confidence: 91%
“…In rat brain in vitro, PCBs inhibited mitochondrial Ca2+ uptake (Kodavanti and Ward 2005 ), while in brain and liver cells of rats, significant reductions of oxygen consumption and respiratory chain complexes II and III have been demonstrated (Ounnas et al 2016 ). In addition, induction of mitochondria dysfunction by PCBs in SH-SY5Y (neuroblastoma cells) and Vero cells (kidney epithelial cell line) was recently shown by Shen et al ( 2011 ) and Cocco et al ( 2015 ). In the present study, we reported modulation of ERRs expression and function as well as ultrastructure of mitochondria in Leydig cells treated with PCBs.…”
Section: Discussionmentioning
confidence: 80%
“…PCBs have been shown to induce mitochondrial dysfunction and oxidative stress in vitro 40 and upon application in vivo , reduce the surfaces and volume density of mitochondria while maintaining their numbers at a constant rate. As a consequence, the energy supply of mitochondria were reduced, as could be demonstrated by incubating Jurkat T cells with OH-PCBs at a concentration of 500 nM (Fig.…”
Section: Discussionmentioning
confidence: 99%